The Reproduction and Reinterpretation of Kandinsky's 'Yellow-Red-Blue' Painting - Turan Enginoğlu; Burcu Meral Tezeren; Ekin Boztaş; Kemal Yürümezoğlu (Art Time)
This article examines the interdisciplinary potential between art and science through the reproduction of Wassily Kandinsky's 1925 masterpiece "Yellow-Red-Blue" using the primary colors of paint—Cyan, Magenta, and Yellow (CMY). The research aims to bridge the gap between traditional artistic expression and scientific methodology in a way that informs and enhances both art creation and art education through contemporary color theory. Kandinsky's original "Yellow-Red-Blue" masterpiece uses Red, Yellow, and Blue (RYB) to symbolize the vibrancy and emotional depth achievable through color contrasts and harmonies. In contrast, this study's reproduction using CMY aims to uncover new perspectives on color interactions, perception, and educational values. The research quantitatively evaluates changes in hue, saturation, and brightness when RYB is replaced with CMY, utilizing a methodological approach based on scientific color knowledge, including the color spectrum and comparative analysis. The reproduction process is documented to assess the impact of these color changes on the viewer's perceptual and emotional experience. The findings of the research are expected to contribute to a deeper understanding of Kandinsky's techniques and the theoretical foundations of color use in art. Additionally, the findings are integrated into the STEAM education framework, which promotes pedagogical approaches where art and science dynamically interact.